Higher burden of supraventricular ectopic complexes early after catheter ablation for atrial fibrillation is associated with increased risk of recurrent atrial fibrillation. Issue 1 (7th December 2016) - Alhede, Christina; Johannessen, Arne; Dixen, Ulrik; Jensen, Jan S; Raatikainen, Pekka; Hindricks, Gerhard; Walfridsson, Håkan; Kongstad, Ole; Pehrson, Steen; Englund, Anders; Hartikainen, Juha; Hansen, Peter S; et al.
Abstract: Aims: Early identification of patients who could benefit from early re-intervention after catheter ablation is highly warranted. Our aim was to investigate the association between post-procedural burden of supraventricular ectopic complexes (SVEC) and the risk of long-term atrial fibrillation (AF) recurrence. Methods and results: A total of 125 patients undergoing catheter ablation for AF were included. Patients underwent 7-day Holter recordings immediately post-procedural. The number of SVEC in post-procedural Holter recordings was categorized into quartiles: 0–72, 73–212, 213–782 and ≥ 783 SVEC/day. Long-term AF recurrence was defined as a combined endpoint of AF ≥ 1 min during follow-up Holter recordings, cardioversion or hospitalization for AF after a 3-month blanking period and within 24 months of follow-up. High post-procedural supraventricular ectopy burden was associated with an increased risk of long-term AF recurrence in a dose-dependent manner (≥ 783 SVEC: HR 4.6 [1.9–11.5], P < 0.001) irrespective of AF recurrence during the blanking period or other risk factors. In patients with early AF recurrence < 90 days after catheter ablation ectopy burden was also highly predictive of long-term AF recurrence (SVEC ≥ 213: HR 3.0 [1.3–6.7], P = 0.007). Correspondingly, patients with early AF recurrence but low ectopy burden remained at low risk of long-term AF recurrence after the blanking period. Conclusion: Our results indicate that post-procedural ectopy burden is highly associated with long-term AF recurrence and could be a potent risk marker for selection of patients for early re-ablation. Development of future ablation risk stratification and strategies should include focus on post-procedural ectopy burden.